(779) Foreign Loans and Economic Development / Part 2 : The Fixed Annuity Principles القروض الأجنبية والتنمية الاقتصادية: الجزء الثاني: مبدأ القسط الثابت - M. El-Imam, M. (INP, 2023)
This study analyzes the mathematical formula for fixed annuities and the impact of single loans on cash flows. It explores the formulas with time lags and loan replacements, identifying advantage criteria in both the presence and absence of lags. The replacement rule is introduced to optimize loan repayment strategies, while the effects of postponing repayments on financial performance are evaluated. The findings highlight how strategic loan management can minimize overall costs and enhance financial sustainability. The study concludes with recommendations on applying these insights to improve investment and borrowing decisions.